Analysing the effects of OOP helper application - Udvaros, József (Teaching Mathematics and Computer Science, 2017)
Nowadays students of secondary schools are familiar with the usage of computer very soon, lot of them are even capable of handling user applications very cleverly. This is satisfying for most of them. Those who imagine their future in programming or system developing, need to have deeper knowledge about object oriented programming, however, students do have it at very low level or not at all. We want to make sure whether this suppose is true, so different examinations have recently been made at Slovakian secondary schools with Hungarian teaching language. We have reached a conclusion that the students’ knowledge of object oriented programming is deficient. We could achieve better results by using proper applications as a visual aid. In this paper we examine the efficiency of an application made by us.